Real-world outcomes on platinum-containing chemotherapy for EGFR-mutated advanced nonsquamous NSCLC with prior exposure to EGFR tyrosine kinase inhibitors - Halmos, Balazs; Rai, Pragya; Min, Jae; Hu, Xiaohan; Chirovsky, Diana; Shamoun, Mark; Zhao, Bin (Frontiers in Oncology, 2024)
Background Front-line therapy with an EGFR tyrosine kinase inhibitor (TKI) is the standard of care for treating patients with advanced nonsquamous NSCLC with the common sensitizing EGFR exon 19 deletion and exon 21 L858R point mutations. However, EGFR TKI resistance inevitably develops. The optimal subsequent therapy remains to be identified, although platinum-containing chemotherapy regimens are often administered. Our objectives were to describe baseline characteristics, survival, and subsequent treatment patterns for patients with advanced nonsquamous NSCLC with EGFR exon 19 deletion or L858R mutation who received a platinum-based combination regimen after front-line EGFR TKI therapy. Methods This retrospective study used a nationwide electronic health record-derived deidentified database to select adult patients with advanced nonsquamous NSCLC, evidence of EGFR exon 19 deletion or L858R mutation, and ECOG performance status of 0-2 who initiated platinum-containing chemotherapy, with or without concomitant immunotherapy, from 1-January-2011 to 30-June-2020 following receipt of any EGFR TKI as first-line therapy or, alternatively, a first- or second-generation EGFR TKI (erlotinib, afatinib, gefitinib, dacomitinib) as first-line therapy followed by the third-generation EGFR TKI osimertinib as second-line therapy. Data cut-off was 30-June-2022. The Kaplan-Meier method was used to estimate overall survival (OS) after initiation of pemetrexed-platinum (n=119) or any platinum-based combination regimen (platinum cohort; n=311). Results The two cohorts included two-thirds women (65%-66%) and 57%-58% nonsmokers; median ages were 66 and 65 years in pemetrexed-platinum and platinum cohorts, respectively. Median OS was 10.3 months (95% CI, 8.1-13.9) from pemetrexed-platinum initiation and 12.4 months (95% CI, 10.2-15.2) from platinum initiation; 12-month survival rates were 48% and 51%, respectively; 260 patients (84%) had died by the end of the study. Conclusion The suboptimal survival outcomes recorded in this study demonstrate the unmet need to identify more effective subsequent treatment regimens for patients with EGFR-mutated advanced nonsquamous NSCLC after EGFR TKI resistance develops.